PENGARUH LIVE STREAMING, ONLINE CUSTOMER REVIEW DAN INFLUENCER TERHADAP NIAT BELI PADA E-COMMERCE SHOPEE SURVEI GENERASI Z DI YOGYAKARTA - Suganda, Intan Rizkiawati; Religia, Yoga (Universitas Mercu Buana, 2024)
The development of social media is currently very rapid and has become a well-known phenomenon in society, this provides opportunities for business people to promote their products and services. By using various platforms such as Instagram, Shopee, Twitter etc., companies can interact directly with consumers, receive feedback and promote products effectively and efficiently. Shopee is one of the most popular e-commerce sites, with an average of 216 million visits per month in the third quarter of 2023, an increase of 30% from the previous quarter. This research examines the influence of live streaming, consumer reviews and influencers on purchase intentions on Shopee e-commerce among generation Z in Yogyakarta. The sample in this study consisted of 100 respondents. The research method used is quantitative and the instrument used in this research is a questionnaire prepared on a Likert scale and the data is processed using SmartPLS. The results of this research analysis produce: (1) Live streaming has a significant positive effect on purchase intentions on e-commerce Shopee generation Z in Yogyakarta; (2) Online customer reviews have a significant positive effect on purchase intentions on Generation Z e-commerce Shopee in Yogyakarta; and (3) influencers have a significant positive effect on purchase intentions on e-commerce Shopee generation Z in Yogyakarta.Keywords: live straming, online customer review, influencer, purchase intention.